Validation Based on Content To Measuring Carrer Decission Readiness - Pratama, Entol Bugi; Purwono, Urip; Yudiana, Whisnu (Journal of Research and Measurement in Psychology: JPPP, 2021)
Adolescent are required to be ready to make career decisions, such as choosing the right college major. Career decision readiness is defined as the capability of an individual to make appropriate career choice while taking into account the complexity of family, social, economic, and organizational factors that influence an individual’s career development. This study aims to find the content validity of measuring career decision readiness based on high school student condition in Indonesia . An expert review process from three lecturers and six educational psychology practitioners was carried out to obtain evidence of validity based on content. The expert review process is divided into three stages, the first stage of reviewing 160 items by three lecturers, the second stage of revising the items, and the third stage of the review process by six educational psychology practitioners.The results of the research showed that 74 items for measuring career decision readiness had an I-CVI value above 0.78 and an S-CVI value of 0.98. Further research needs to be done by testing measuring instruments and collecting data to find other evidence of validity and gathering norms.